Níveis de t3 e t4 livres em pacientes portadores de hipotireoidismo primário em tratamento com levotiroxina - Wiliam Pedrosa de Lima (2011)
Hypothyroidism is a disease that affects a significant number of people. Approximately 2% of adult women and 0.2% of men are affected. The disease can be classified into primary (thyroid cause) and secondary or terciary (pituitary or hypothalamic cause) hypothyroidism. The diagnosis is generally made by laboratory investigation since clinical characteristics show low sensitivity and specificity. At present, primary hypothyroidism is basically treated by levothyroxine replacement therapy. Elevated T4 concentrations have been observed during treatment of hypothyroidism even in patients with normal TSH levels. Despite the knowledge that T4 concentrations may increase during treatment of hypothyroidism, there is disagreement once they exceed the upper reference limit considering that TSH remains normal in these patients. This profile of normal TSH and elevated free T4 is also observed in other clinical conditions (familial dysalbuminemic hyperthyroxinemia, resistance to thyroid hormones) and during the use of certain drugs (furosemide). Few studies have so far determined the proportion of altered T4 levels during treatment of primary hypothyroidism. Variations ranging from 3.6% to 32% have been reported. However, these studies used T4 reference ranges pre-established by the laboratories, did not employ third-generation TSH assays as a biochemical control criteria, and involved patients who ingested high doses of thyroid hormone. The present study evaluated 52 patients with primary hypothyroidism and normal TSH and compared them to a control group of 95 subjects without hypothyroidism. This group permitted the creation of the reference range for the local population. The levothyroxine dose found in the present study was the lowest among those reported previously, only 78 ± 23 g/day. The percentage of patients who regularly used levothyroxine and who presented free T4 levels above the upper reference limit was 19,2%. Mean free T4 concentrations were also higher in the treated group than in the control group. Free T3 levels were lower in the treated group. In conclusion, patients treated with levothyroxine and with normal TSH levels frequently present free T4 levels above the upper reference limit, elevated free T4 concentrations, and low free T3 levels when compared to a control group. As expected, the free T4/free T3 ratio was higher in patients using levothyroxine